The model selection of propeller turbine construction using Analytical Hierarchy Process (AHP) - Dedi Wardianto; Mafrizal Mafrizal; Sufiyanto Sufiyanto; Rudi Kurniawan Arief; Herry Agung Prabowo; Irfan Hilmy (SINERGI, 2023)
This study aimed to develop an innovative propeller turbine design to facilitate easy manufacturing and maintenance processes, leading to a reduction in costs. Furthermore, the Analytical Hierarchy Process (AHP) method was employed to identify the most optimal model and design for the propeller turbine. Problem-solving within the AHP framework was guided by three fundamental principles, namely decomposition, Comparative Judgment, and Logical Consistency. The procedure included problem decomposition, assessment/ weighting to compare elements, matrix preparation and consistency testing, setting priorities for each hierarchy, priority synthesis, and decision-making. To establish a benchmark, three types of propeller turbines currently available in the market served as references. Meanwhile, the selection criteria for the model were based on several factors, including power factor, time efficiency, ease of manufacture, as well as production and maintenance costs. Considering the criteria, modifications were made to these reference models, resulting in the development of alternatives, denoted as A, B, and C. The results showed that alternative type A as the most suitable choice for further development. Therefore, this particular design was granted foremost priority to develop a low-head generator that possessed ease of manufacturing and surpassed alternative models in terms of feasibility.